2022
DOI: 10.3389/fneur.2022.834469
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Therapeutic Anticoagulation in COVID-19 Patients With Acute Ischemic Stroke. A Retrospective Multicenter Study

Abstract: BackgroundAcute ischemic stroke (AIS) is a possible complication of coronavirus disease 2019 (COVID-19) infection. Although peculiar clinical features and underlying specific mechanisms of thrombogenesis have been suggested so far, there is no consensus on the appropriate vascular preventive drug regimen in patients with COVID-19.Aim and MethodsFrom a larger clinical series of consecutive acute ischemic strokes related to COVID-19 admitted to three cerebrovascular units in Northern Italy, herein, we describe t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Though a significant increase of FDPs can conceivably result in viscoelastic changes, these in of themselves would be too small in size to explain the observed spatial heterogeneities, and would not explain the lack of any significant hysteresis in up-down temperature sweeps observed (which also rule out the denaturing of proteins). Our observations are somewhat surprising given that our samples were collected and stored in anticoagulation tubes (Methods), although reports have hinted at the reduced effectiveness of anticoagulants in COVID-19 patients 31,32 . While ultrastructural and biochemical studies on suspensions is still needed, one can speculate whether these might be related to crosslinked microfibrin/fibrin microclots reported to exist in COVID patient samples 33 .…”
Section: Discussionmentioning
confidence: 79%
“…Though a significant increase of FDPs can conceivably result in viscoelastic changes, these in of themselves would be too small in size to explain the observed spatial heterogeneities, and would not explain the lack of any significant hysteresis in up-down temperature sweeps observed (which also rule out the denaturing of proteins). Our observations are somewhat surprising given that our samples were collected and stored in anticoagulation tubes (Methods), although reports have hinted at the reduced effectiveness of anticoagulants in COVID-19 patients 31,32 . While ultrastructural and biochemical studies on suspensions is still needed, one can speculate whether these might be related to crosslinked microfibrin/fibrin microclots reported to exist in COVID patient samples 33 .…”
Section: Discussionmentioning
confidence: 79%
“…The American Society of Hematology (ASH) guidelines recommended prophylactic dose anticoagulation over intermediate and therapeutic intensity regimens due to small absolute risk difference, with no preference for any specific agent [ 108 ]. A case series of 17 patients receiving therapeutic doses of various anticoagulation medications pointed out the probability of resistance due to COVID-19 coagulopathy [ 109 ]. In a study comparing thrombotic outcomes between 108 patients receiving prophylactic dose and 71 receiving therapeutic dose heparin, the latter presented no AIS, while in the former group 6 patients (5.6%) eventually developed AIS.…”
Section: Management Of Patients With Cerebrovascular Sequelae During ...mentioning
confidence: 99%
“…Of note, the occurrence rate of arterial or venous thromboembolism in hospitalized COVID-19 patients has been reported to be between 8% and 31% despite the fact that prophylactic anticoagulant therapy was adopted [52,53] . A multicenter study conducted in Italy has reported that COVID-19 patients to whom stroke occurred despite the use of anticoagulant therapy had a worse clinical outcome, along with 64.7% of fatality rate [54] . The treatment for stroke is similarly administered to patients with or without COVID-19; however, there are few studies about the safety and feasibility of thrombectomy treatment in COVID-19 patients with acute ischemic stroke.…”
Section: Cerebrovascular Diseasesmentioning
confidence: 99%